Prevalence of bacterial vaginosis and factors associated among women who have sex with women - Mariana Alice de Oliveira Ignacio; Juliane Andrade; Ana Paula Freneda de Freitas; Gabriel Vitor da Silva Pinto; Marcia Guimarães da Silva; Marli Teresinha Cassamassimo Duarte (Universidade de São Paulo, 2018)
ABSTRACT Objective: to describe the prevalence of bacterial vaginosis and factors associated among women who have sex with women. Method: cross-sectional, descriptive and analytical study with 150 women. The vaginal microbiota profile was analyzed by microscopic examination of vaginal swabs according to the Gram method. Endocervical samples were collected with cytobrush for the investigation of endocervicitis by Chlamydia trachomatis. The polymerase chain reaction was used to diagnosis Human Papillomavirus infection. Socio-demographic data, sexual behavior and clinical history were obtained through an interview. Logistic regression was performed to identify risk factors independently associated with bacterial vaginosis. Results: among the 150 participants, 71 (47.3%) presented some alteration in the vaginal microbiota, 54 (36.0%) bacterial vaginosis and 12 (8.0%) Flora II. The variable independently associated with bacterial vaginosis was the use of sexual accessories [2.37(1.13-4.97), p=0.022]. Conclusion: the high prevalence of bacterial vaginosis among women who have sex with women indicates the need for screening this population and association between use of sexual accessories and this disease suggests the possibility of transmission of sexual fluids between the partners during the sexual act, which demonstrates the need for educational actions on sexual and reproductive health.